The correct answer is the third option.
Answer:
x = -2
Step-by-step explanation:
So we are given the equation -3(3x + 3) = -2x + 5 and we are solving for x. We will have to try to get the equation into the form x = _. That would be our answer.
-3(3x + 3) = -2x + 5
Distribute the -3 on the left side.
-9x - 9 = -2x + 5
Add 2x to both sides to get rid of the -2x on the right side.
-9x - 9 + 2x = 5
Simplify.
-7x - 9 = 5
Add 9 to both sides to get rid of the - 9 on the left side.
-7x = 5 + 9
Simplify.
-7x = 14
Divide both sides by -7 to get rid of the coefficient of -7 on the left side.
x = 14 ÷ (-7)
Simplify.
x = -2
The answer is x = -2.
I hope you find my answer helpful. :)
Quite simple when you take out the useless stuff you added in. Its 16
Sorry, I haven't learned this yet ;-;